MANAGEMENT OF ORAL LESIONS ASSOCIATED WITH CARBAMAZEPINE RELATED STEVENS-JOHNSON SYNDROME / TOXIC EPIDERMAL NECROLYSIS OVERLAP PATIENT: PENATALAKSANAAN LESI ORAL TERKAIT DENGAN PASIEN SINDROM STEVENS-JOHNSON DENGAN CARBAMAZEPINE-RELATED / NEKROLISIS RACUN EPIDERMAL YANG TUMPANG TINDIH - Puspasari, Dewi; Sufiawati, Irna (Dentika: Dental Journal, 2016)
Stevens“Johnson syndrome (SJS)/ Toxic Epidermal Necrolysis (TEN) are acute, self-limited, potentially life-threatening mucocutaneous disease. Oral mucosal involvement manifest as extensive erosions and haemorrhagic crusting, which can interfere oral functions causing odynophagia, inability to tolerate solid foods, and increased aspiration risk. A 40-year-old female patient was referred from Dermatology and Venereology department with diagnosis SJS/TEN overlap. The patient complained mouth opening difficulty due to mouth and lip sores. Drug history revealed positive intake of carbamazepine. Extraoral examination revealed multiple diffuse discrete facial lesions, conjunctival hyperemia, erosions and hemorrhagic crusting lips. Intraoral examination revealed white yellowish plaque, and erosions on buccal mucosa, palate, floor of the mouth, dorsal, ventral, and lateral tongue. Laboratory investigation revealed decrease of haemoglobin, hematocrite, Mean Corpuscular Volume (MCV), Mean Corpuscular Hemoglobin (MCH), thrombocyte, eosinophil, band of eosinophil, lymphocyte, natrium, potassium, and calcium. Oral lesions associated with SJS/TEN overlap diagnosis was made. Chlorhexidine gluconate 0,1%, nystatin oral suspension, vitamin B12, folic acid, and corticosteroid unguent compounding were given, which showed improvement of oral lesions in 3 weeks. SJS/TEN are the same disease spectrum of delayed hypersensitivity reaction leading to keratinocyte apoptosis through cytotoxic T-cell mediated Fas-Fas ligand, perforin/ granzyme B, and granulysin, which distinguished primarily by severity and percentage of total body surface area involved.Currently, an optimal treatment standard for SJS/TEN patients remains unavailable. Oral lesions management play significant role in enhancing patients’ quality of life and achieving better prognosis in SJS/TEN overlap patients through multidisciplinary approach.